Pembuatan Arang Aktif Dari Limbah Sekam Padi Sebagai Adsorben Dan Penyedia Unsur Hara - Fatmayati Fatmayati (Jurnal Sains dan Ilmu Terapan, 2018)
Sources of raw materials that can be made into activated charcoal come from animals, plants, waste or minerals that contain carbon. In 2012 rice production was estimated at 68.59 million tons of GKG, an increase of 2.84 million tons (4.31 percent) compared to 2011. Based on the above conditions and the potential of rice husk as a raw material for activated charcoal, it is necessary to process rice husk so that it can be used as activated charcoal. The purpose of this study was to determine the processing of rice husk into activated charcoal and the characteristics of the activated charcoal produced and to determine the potential of charcoal as an adsorbent and nutrient provider. The method used in this study refers to SNI 06-3730-1995. The fixed variable was the activation process of rice husk with 0.5M NaOH at a temperature of 800C for 2 hours, while the changing variable was the temperature of 4000C and 5000C with carbonization times of 30,45,60,75,90,105 and 120 minutes